2020
DOI: 10.1093/humrep/deaa138
|View full text |Cite
|
Sign up to set email alerts
|

Time as an outcome measure in fertility-related clinical studies: long-awaited

Abstract: ABSTRACT Time taken to achieve a live birth is an important consideration that is central to managing patient expectations during infertility treatment. However, time-related endpoints are not reported as standard in the majority of fertility-related clinical studies and there is no internationally recognized consensus definition for such endpoints. There is, therefore, a need for meaningful discussions around the selection of appropriate time-related treatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…The recommended secondary endpoints include the number of oocytes retrieved (both overall and metaphase II oocytes), the number of embryos generated, the FOI ( 20 ), and how effective a specific intervention was in achieving the number of oocytes estimated by the ART calculator ( 30 ). Time to live birth (TTLB) is an additional outcome that should be considered, given that a shorter time in achieving a live birth is a reflection of the clinical and cost-effectiveness of any intervention ( 65 ). Also, in observational studies, particularly those involving big analytics, the frequency of patients fitting each POSEIDON group should be reported, including –if possible– a control group of non-POSEIDON patients for comparison.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The recommended secondary endpoints include the number of oocytes retrieved (both overall and metaphase II oocytes), the number of embryos generated, the FOI ( 20 ), and how effective a specific intervention was in achieving the number of oocytes estimated by the ART calculator ( 30 ). Time to live birth (TTLB) is an additional outcome that should be considered, given that a shorter time in achieving a live birth is a reflection of the clinical and cost-effectiveness of any intervention ( 65 ). Also, in observational studies, particularly those involving big analytics, the frequency of patients fitting each POSEIDON group should be reported, including –if possible– a control group of non-POSEIDON patients for comparison.…”
Section: Resultsmentioning
confidence: 99%
“…However, the use of such endpoints in preference over CDR in POSEIDON studies should always be justified. When considering time-to-pregnancy (TTP) or TTLB as an outcome, the start time point should be oocyte retrieval and the end time point the clinical pregnancy (TTP) or live birth (TTLB) ( 65 ). As POSEIDON interventions should aim to increase the oocyte yield for the low prognosis patients, this justifies the start point from oocyte retrieval for TTP and TTLB outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the intricacy of IVF, the time to live delivery may be longer than with IUI. To compare the time spent for the two procedures, we utilized the Kaplan-Meier curves, which is recommended for evaluating the CLBR across time in clinical investigations [13]. The ndings showed that when the two groups were censored at 180 days, the live birth rates were not substantially different.…”
Section: Discussionmentioning
confidence: 99%
“…The first is to consider the effect of an intervention on cumulative live birth rates (CLBR), a term which refers to the proportion of patients having a live birth following some maximum number of treatment attempts or after a given period of follow-up time (Malizia et al 2009). The second is to consider the effect on time to live birth, which refers to how long it takes to have a live birth (Sunkara et al 2020). The two concepts are quite closely related, and in fact, CLBR may be (and often is) estimated using methods for time-toevent analysis.…”
Section: Evaluating Treatment Outcomes Over Multiple Treatment Attemptsmentioning
confidence: 99%
“…In recognition of the fact that fertility treatment is often emotionally and financially burdensome, there is a current interest in identifying treatments and treatment strategies that reduce the duration from treatment initiation to live birth (Sunkara et al 2020). This focus on a patientcentred outcome is laudable.…”
Section: Errors In the Analysis Of Time To Live Birthmentioning
confidence: 99%